Social change and psychological harmony among families of people with special needs in Palestinian society: A Study on a sample of families of people with special needs in the city of Nablus – Palestine - Alawneh, Abdelmajid Nayif (Journal of Humanities & Social Sciences, 2020)
The aim of this research is to know the extent of the impact of the category of people with special needs on family members, specifically on the levels of social change and psychological compatibility in terms of showing the factors specific to this group, and clarify the nature of the relationship between this group and the variables of social background for them and their families, and identify their characteristics, and the extent of the impact of their presence on individuals Their families, and this research used the descriptive analytical method and the questionnaire tool, in addition to that the sample taken in this research amounted to (177) from the families of the Palestinian community in which there is an individual with special needs specifically from the people of this category in one of the Palestinian cities. In the northern West Bank, which is the city of Nablus, the researcher used the sample with its intended type. It was found that the majority of individuals with special needs are male, small and medium ages, and those with an average degree of disability as a result of life reasons and their duration is mostly average as well. As for the data on the degree of social change, it came in a way between medium and large and amounted to (4.75%) in the various fields of this social change, which was represented by the change in life, which came with a value of (79.1%), and the change in values ​​came with a value (78.5%) The change in behavior came with a value of (75.7%), the change in the degree of solicitation and the extent of receptivity in assisting people with disabilities, which came with a value of (73.4%), and the change in culture represented by the ability to adapt and the degree of vulnerability came with a value of (70.1%). As for the degree of psychological compatibility, it came very significantly, and reached a value of (88%) as a result of being affected by the existing disability, and that psychological compatibility represented in all areas of this compatibility, such as a change in feeling and feeling, which came with a value that reached (91%) And the extent of the psychological stress, which came with a value of (90.4%), the extent of the individual’s feeling of comfort or unhappiness and came with a value of (88.7%), the nature of the treatment with family members came with a value of (85.3%), and the extent of the presence of psychological stress that came with a value of (83.1%). This study reached a number of results, namely that there is a relationship between the social variables of individuals in need T own degrees of social change and psychological compatibility of the families of this category of people with disabilities such as sex, age, and degree of disability, and the cause of disability, and the duration of disability, the study recommended the need for cooperation between people with disabilities and their families, and the distribution of tasks among members of families with special needs to help them.